Association of BAFF, APRIL serum levels, BAFF-R, TACI and BCMA expression on peripheral B-cell subsets with clinical manifestations in systemic lupus erythematosus. (May 2016) - Salazar-Camarena, D C; Ortiz-Lazareno, P C; Cruz, A; Oregon-Romero, E; Machado-Contreras, J R; Muñoz-Valle, J F; Orozco-López, M; Marín-Rosales, M; Palafox-Sánchez, C A
Objective: B-cell-activating factor (BAFF) and a proliferation-inducing ligand (APRIL) signaling pathways regulate B-cell survival through interactions with their receptors BAFF-R, TACI and BCMA. We evaluated the association of these ligands/receptors on B-cell subsets according to clinical manifestations of systemic lupus erythematosus (SLE). Methods: BAFF and APRIL serum concentrations were measured in 30 SLE patients by enzyme-linked immunosorbent assay. The BAFF-R, TACI and BCMA expression was analyzed on each B cell subset (CD19 + CD27-CD38–/ + naïve; CD19 + CD27 + CD38–/ + memory; CD19 + CD27-CD38 + + immature and CD19 + CD27 + CD38 + + plasma cells) by flow cytometry, and compared among patients with different clinical manifestations as well as healthy controls (HCs). Results: Serum BAFF and APRIL levels were high in SLE patients and correlated with the Mex-SLEDAI disease activity index ( r = 0.584; p = 0.001 and r = 0.456; p = 0.011, respectively). The SLE patients showed an increased proportion of memory and plasma B cells ( p < 0.05). BAFF-R, TACI and BCMA expression in SLE patients was decreased in almost all B cell subsets compared to HCs ( p < 0.05). A lower BCMA expression was associated with severe disease activity, glomerulonephritis, serositis and hemolytic anemia ( p < 0.01). BCMA expression showed a negative correlation with Mex-SLEDAI score ( r = –0.494, p = 0.006). Conclusions: Decreased BCMA expression on peripheral B cells according to severe disease activity suggests that BCMA plays an important regulating role in B-cell hyperactivity and immune tolerance homeostasis in SLE patients.